Taxonomy, ecology and control of thalassina mud lobsters on Carey Island and Kelanang shore (Peninsular Malaysia) / Moh Heng Hing - Moh , Heng Hing (2016)
Thalassinid mud lobsters are large burrowing crustaceans commonly found on mangrove shores. They are not well studied due to their cryptic nature and subterranean habit. Mangrove land reclamation puts this enigmatic creature at odds with humans where their burrowing activities wreck coastal dykes and culture ponds. This study investigated the species of mud lobsters in Malaysia, and their abundance and distribution in relation to environmental factors on Kelanang shore and particularly, Carey Island, where coastal dykes are built to protect largely oil palm estates. Thus, a goal of this study was to find environmental-friendly ways to control mud lobster infestations on earthen dykes. Three species of Thalassina, namely, Thalassina anomala Herbst, 1804, Thalasssina gracilis Dana, 1852 and Thalassina kelanang Moh & Chong, 2009 were described and compared to the Australian species, Thalassina squamifera De Man, 1915. Morphological features of the carapace, rostrum, scaphocerite, abdominal pleura and sternites, and petasma was used to distinguish between the newly described species, T. kelanang from T. squamifera which closely resembles it morphologically, as well as the other species. These four species of Thalassina were further verified as distinct by discriminant analysis of their morphological traits and by three molecular gene markers (PEPCK, NaK, and COI). Both approaches agree that T. anomala and T. gracilis are the most distant pair among the four species. Molecular analysis of the combined markers shows that the four species of Thalassina belong to a monophyletic clade, and that T. squamifera and T. kelanang are two closely similar, but distinct, species. Three sympatric species of mud lobsters were spatially distributed along the mangrove shore, occurring in combinations of T. anomala with T. kelanang (Kelanang) or T. gracilis (Carey Island). Spatial partitioning of these species was strongly driven by environmental factors such as tidal inundation, salinity and substrate characteristics. Competitive exclusion was hypothesized with the more aggressive T. kelanang living on the lower shore and T. anomala on the upper shore. T. gracilis (genetically closest to T. kelanang) was spatially partitioned from T. kelanang by its greater tolerance to salinity fluctuations in the mid-estuary where it occupied a similar elevation in tidal height as T. kelanang. The distribution of mud lobster (T. anomala) mounds along the entire dyke perimeter of Carey Island was not random with high densities (up to 70 mounds/100m bund length) occurring at the northeastern horn of the island and near Air Hitam village south of the island. T. anomala first invaded the coastal dyke on the river side of the bund at the highest spring tide level. The animal then tunneled down to the bund bottom at the opposite or landward side, before venturing farther (up to 10m) into the oil palm plantation, as long as they could access water. Mud lobster burrows on the bund or plantation could reach 60cm in height and 1.2m in depth. Experimental planting of different species of grass vegetation on the dyke to obstruct the passage (vertical barrier) or exit (horizontal barrier) of the mud lobster showed that a combination of Chrysopogon zizanioides (Vetiver) and Cyanodon dactylon grasses is the most effective way to control mud lobster infestations without the use of toxic chemicals. The study shows the mangrove shore as the endemic habitat for three species of Thalassina in Malaysia. Coastal reclamation of mangrove forests destroys their natural habitat and cuts off the path of migration of T. anomala from sea to the landside of mangrove forests. This results in Thalassina larvae settling and colonizing coastal dykes constructed by humans to prevent sea water intrusion.